Diet Diversity of Complementary Foods: A Case Study of Mulot Division, Narok County - Ronoh , Amos; M. Were, Gertrude (African Journal of Education,Science and Technology (AJEST), 2015)
Diet diversity is an important element of a high quality diet. Intake of a varied diet increases the chances of a person meeting their essential nutrient intake. Young children in particular need energy and nutrient-dense foods to meet their dietary needs. According to literature, diets high in diversity are recommended for the first two years in life as this stage involves rapid physical, cognitive and social development. The purpose of this study was to investigate the diet diversity of complementary feeds in children aged 6-59 months in Mulot Division. A descriptive research design was adopted in this study. Four villages to participate in this study were randomly selected. A care giver with a child within the target group was randomly selected. Interview schedules generated data on child feeding practices. Data was entered into and analyzed using the Statistical Package for Social Sciences (SPSS) computer software Version 20 (2007). Tests run were Spearman‟s correlation analysis and Analysis of variance (ANOVA). A p-value of p<0.05 was considered significant. The results showed that 83% of the respondents had a high diet diversity score, while the rest had a medium diet diversity score. No child had a poor score on diet diversity. Results also showed that 41.7% of children were still being breastfed while 61.7% were bottle fed. Sixty-six (66 %) percent of the children had been started on complementary foods, while 56% had been exclusively breast-fed. There was a significant relationship between diet quality and the diet diversity score (p<0.05). Most of the children had an adequate intake of nutrient by the use of the 7 day recall. No significant correlation between socio-economic status with diet diversity was found (p<0.05). Most children were fed on a medium diverse diet; a majority of the mothers were not compliant with the recommended child feeding practices, particularly breastfeeding beyond six months even after introduction of complementary foods and bottle feeding. Policies should be formulated to educate mothers and care givers on the importance of exclusive breastfeeding and discourage bottle feeding of young children.